Simple Calculation of the Radiation Flux Distribution for Brachytherapy Using Microsoft Excel - Sarah Ismi Kamilah; Freddy Haryanto (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2015)
One of the therapies used to destroy cancer cells is brachytherapy. This type of therapy has a radioactive source located in right position or near the cancer cells. In fact, brachytherapy is always faced a high risk for patients’ safety. Calculation of radiation dose distribution is one tool to optimized therapy. However, mostly people do not understand about it, even medician. This is the background from author to do simple study about calculation of the radiation particle flux distribution and make simple concept about it. The method in this study used coordinate transform to have formula. This calculation based on the geometry of various radioactive sources, being brought closer to the point and line. The formula used to have contour curves with simple computing in Excel. Contour curves from this radiation particle flux distribution is in two – dimensional form. The result showed that isodose contours curves from research used excel were similar with references in quantitatively. This way is very simple and people can easily understand the basic concept of calculate from radiation particle flux distribution.Keywords: Brachytherapy, Flux, Radioactive Source Geometry, Isodose, Microsoft Excel